Miskonsepsi Siswa SMA Materi Osmoregulasi & Sistem Ekskresi Sebagai Dasar Pengembangan Bahan Ajar: (Misconceptions of High School Students on Osmoregulation & Excretory System as a Basis for Development of Teaching Materials) - Ridwan, Ridwan; Amprasto, Amprasto; Widodo, Ari; Azizah, Cici Nur (BIODIK, 2024)
This study aims to identify the misconceptions experienced by grade XI high school students on osmoregulation and excretory system material, and analyze the sources that cause these misconceptions. A good understanding of the concepts in this material is very important because it is related to the physiological processes that occur in the human body. This study used descriptive qualitative method with data collection techniques through multiple-choice diagnostic tests through google form and in-depth interviews as well as documentation and literacy studies. The research subjects amounted to 283 grade XI students from three high schools in the West Sumatra city area, namely SMA N 1 Payakumbuh, SMA N 2 Linggo Sari Baganti, SMA N 3 Muaro Jambi, SMA N 3 South Solok, SMA N 2 Sipora Kab. Kep. Mentawai. The results showed that most students had misconceptions on concepts such as osmoregulation mechanism & Excretion System. The sources of misconceptions identified include initial misconceptions, incomplete teacher explanations, inadequate textbooks, and difficulties in visualizing complex processes. These findings form the basis for developing teaching materials that are more effective and contextualized in correcting student misconceptions. Key words: Misconception, Osmoregulation, Excretory System, Teaching Materials, Senior high school